2018
DOI: 10.1161/atvbaha.118.310778
|View full text |Cite|
|
Sign up to set email alerts
|

Bmi1-Progenitor Cell Ablation Impairs the Angiogenic Response to Myocardial Infarction

Abstract: Objective- Cardiac progenitor cells reside in the heart in adulthood, although their physiological relevance remains unknown. Here, we demonstrate that after myocardial infarction, adult Bmi1 (B lymphoma Mo-MLV insertion region 1 homolog [PCGF4]) cardiac cells are a key progenitor-like population in cardiac neovascularization during ventricular remodeling. Approach and Results- These cells, which have a strong in vivo differentiation bias, are a mixture of endothelial- and mesenchymal-related cells with in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…To identify Bmi1 + cells in heart sections we used tamoxifen (Tx)-inducible Bmi1 CreERT/+ Rosa26 tdTomato/+ mice (denoted hereafter as Bmi1-cre Tomato ), since GFP signal in cryosections from Bmi1 GFP/+ mice was difficult to distinguish from background. Tomato expression 5 days post-Tx induction in Bmi1-cre Tomato mice resembles GFP expression in Bmi1 GFP/+ mice [12] and the percentage of Tomato + cells was similar to that assessed by fluorescence-activated cell sorting (FACS), indicating that the immunohistochemistry analysis was robust (Fig. S1A).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…To identify Bmi1 + cells in heart sections we used tamoxifen (Tx)-inducible Bmi1 CreERT/+ Rosa26 tdTomato/+ mice (denoted hereafter as Bmi1-cre Tomato ), since GFP signal in cryosections from Bmi1 GFP/+ mice was difficult to distinguish from background. Tomato expression 5 days post-Tx induction in Bmi1-cre Tomato mice resembles GFP expression in Bmi1 GFP/+ mice [12] and the percentage of Tomato + cells was similar to that assessed by fluorescence-activated cell sorting (FACS), indicating that the immunohistochemistry analysis was robust (Fig. S1A).…”
Section: Resultsmentioning
confidence: 63%
“…Many of the endothelial-Bmi1 + DR-cell interactions are challenging to study in vivo . We attempted to mimic these interactions by co-culturing primary Bmi1 + cardiac DR-cells isolated from 5 days Tx-induced adult Bmi1-cre Tomato mice [12] with the endothelial 1g11 cell line [39] and also with primary cardiac endothelial cells (CD31 + ). Co-culture with primary mesenchymal cardiac cells (PDGFRα + ) was used as a control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RT-qPCR analysis showed that BMI1 was preferentially expressed in the YFP + non-CM fraction, and western blot analysis furtherly confirmed that little BMI1 protein was detected in CM fraction and YFP − non-CM compartment [22] . Similarly, Herrero and coworkers used Bmi1 GFP/+ mice to analyze the expression of BMI1 in the heart tissue, and the FACS results showed that BMI1 was highly expressed in a subpopulation of non-CMs in adult mice, in contrast, low levels of BMI1 were detected in the adult myocytes [25] .…”
Section: Novel Roles Of Bmi1 In the Heartmentioning
confidence: 99%